2020
DOI: 10.3390/en13030744
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Hydrolyzed Kraft Pulp by Mono- and Co-Cultures of Yeasts: The Challenge of C6 and C5 Sugars Consumption

Abstract: Second-generation bioethanol production's main bottleneck is the need for a costly and technically difficult pretreatment due to the recalcitrance of lignocellulosic biomass (LCB). Chemical pulping can be considered as a LCB pretreatment since it removes lignin and targets hemicelluloses to some extent. Chemical pulps could be used to produce ethanol. The present study aimed to investigate the batch ethanol production from unbleached Kraft pulp of Eucalyptus globulus by separate hydrolysis and fermentation (SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In comparison to the fermentation performance by the wild S. cerevisiae strain, S. parashehatae showed lower e ciency despite its ability to assimilate C5 sugars. These results are similar to the conversion performance of Pichia stipitis NRRL Y-7124 which was reported to have an ethanol yield and productivity of 0.33 g/ g and 0.34 g/L h, respectively, for a medium containing both pentoses and hexoses [44].…”
Section: Ethanol Production From Hemicellulosic and Enzymatic Hydroly...supporting
confidence: 87%
“…In comparison to the fermentation performance by the wild S. cerevisiae strain, S. parashehatae showed lower e ciency despite its ability to assimilate C5 sugars. These results are similar to the conversion performance of Pichia stipitis NRRL Y-7124 which was reported to have an ethanol yield and productivity of 0.33 g/ g and 0.34 g/L h, respectively, for a medium containing both pentoses and hexoses [44].…”
Section: Ethanol Production From Hemicellulosic and Enzymatic Hydroly...supporting
confidence: 87%
“…A slight decrease in ethanol concentration was observed after reaching its maximum, together with an increase in biomass concentration. Branco et al [ 34 ] already observed a slight increment in biomass concentration when ethanol started to be reassimilated due to the ability of S. cerevisiae to consume ethanol when fermentable sugars dropped. In this regard, biomass concentration still increased after glucose exhaustion also due to consumption of xylose and probably other metabolites present in the hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, 150.33 g ethanol/kg of the SBW was produced when applying the co-culture of S. cerevisiae, P. barkeri, and C. intermedia after 72 h of incubation at 30 °C, pH 5, and 5% of the inoculum concentration. The co-culturing of different yeast strains from various substrates has indeed been proposed as advantageous for the efficiency of the ethanol production process compared to its pure cultures, leading to higher ethanol titers, maximum uptake of carbon sources, and better ethanol yields [14,17,18,[29][30][31][32]. When the same fermentation process was carried out in a 7-L fermenter the productivity increased further, reaching 167.80 ± 0.49 g/kg SBW, which corresponds to an approximately 5% increase of yield compared to the yield obtained from the respective flask experiments.…”
Section: Discussionmentioning
confidence: 99%